Pengaruh Nilai-Nilai Agama Dan Kecerdasan Moral Terhadap Prestasi Belajar Afektif - Bambang Subahri (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2019)
This research was conducted to determine the effect of Religious Values ​​and Moral Intelligence on Students' Affective Learning Achievement, in this case focused on Aqeedah Moral Subjects. The hypothesis in this study is that there is a significant influence of Religious Values ​​namely dimensions: daily, meaning, practice, coping and support. Moral intelligence is the dimensions: acting, telling, standing, keeping, taking, admitting, embracing, actively one's and abilityothers' towards affective learning achievement of students in the subject of aqidah morals. The population in this study were students with age classification of 13-19 years and the sample of 200 students taken using non-probability sampling techniques. To measure religious values, researchers modified 11 dimensions of Fetzer religious values ​​(1999) into 5 dimensions and for moral intelligence researchers used a scale developed from Lennick and Kiel (2011). CFA (Confirmatory Factor Analysis) is used to test the validity of measuring instruments and descriptive analysis is done using SPSS 17.0 and LISREL 8.70. The results showed that there was a significant overall IV effect on learning achievement as DV. The results also showed that the proportion of variance from the learning achievement of Aqeedah Akhlak explained by all independent variables was 60.3%, while the remaining 39.7% was influenced by other variables outside this study. Keywords: Religious Values, Moral Intelligence and Affective Learning Achievement